Quantifying factors affecting MNE's Human Resource Management: Evidence from an emerging economy and implications for HR managers - Enyinda, Chris I.; Opulencia, Maria Jade Catalan; Misajon, Mervyn; Kalyanaran, Gurumurthy (Journal of Eastern European and Central Asian Research (JEECAR), 2019)
Multinational enterprises (MNEs) conduct international business operations around the globe. For the MNEs, operating in today’s global business environment demands human resource departments to be engaged in a variety of activities, including attracting talents, training and development, relocation, repatriation, among others. To contend with the increasing number of issues and challenges in international business environment, MNEs’ must strive to improve their international HRM strategies. As organizations manage subsidiaries across different countries, the approach to human resource management functions must consider the dictate of the local environment where the subsidiary has to operate in order to survive and prosper. The researchers applied a multi-criteria decision making algorithm known as the analytic hierarchy process (AHP) to model the challenges and issues that MNCs’ face as well as the factors impacting the HRM practices. The study explore the challenges by way of literature review and interview of some of the MNEs’ C-level executives.